ANALISIS POLA ASUH AUTHORITATIVE ANAK USIA DINI YANG MEMILIKI IBU TENAGA KERJA WANITA DI SEKOLAH DI BAJANG MLARAK PONOROGO PROPINSI JAWA TIMUR - Mukti Lestari; Dyka Andrian (Prosiding Seminar Nasional Multidisiplin, 2018)
Parenting is the way parents to equip children for the development of life later. This research is a qualitative descriptive study. Data obtained from observation, in-depth interviews and documentation. The data is taken from interactively and continuously data analysis so that the data is saturated. Data analysis includes data reduction, data presentation, and conclusion drawing. The results of this study can be seen that children who have mother TKW still get a good parenting pattern from the surrogate nanny as well as from TKW mothers with authoritative care such as not to curb the freedom of children to play and learn and give freedom in acting as long as it is positive. Children who have mothers TKW in kindergarten Bajang Mlarak Ponorogo well developed, both in the aspects of cognitive, affective and psychomotor. Keywords: Authoritative Authoritative Patterns, Early Childhood, Mother of Female Worker